Vocabulary and Main Idea Reading Intervention Using Text Choice to Improve Content Knowledge and Reading Comprehension of Adolescents With Autism Spectrum Disorder. Issue 1 (January 2021) - Solis, Michael; Reutebuch, Colleen K.; Falcomata, Terry; Steinle, Paul K.; Miller, Veronica L.; Vaughn, Sharon
This simultaneous replication single-case design study investigated a vocabulary and main idea intervention with an aspect of text choice provided to students with autism spectrum disorder (ASD). Five middle school students with ASD participated in two instructional groups taught by school-based personnel. Results were initially mixed. These results were followed by upward and stable trends, indicating a functional relationship between the independent and dependent variables. Social validity measures indicated that students appreciated the opportunity to make choices on text selection.